Presence of Thioxanthones and Their Metabolites in Human Urine and Human Exposure Assessment - Lin Gao; Ling Zhang; Lisha Zhou; Fangfang Ren; Hangbiao Jin; Xiaoyu Wu (Toxics)
Given the widespread environmental presence of thioxanthones (TXs), a class of commonly used photoinitiators, great concerns have been raised regarding their potential human exposure and associated health risks. However, a comprehensive understanding of the total burden of human exposure to these compounds remains limited. To address this gap, the current study collected urine samples from 211 healthy adults in Taizhou City, China, and, for the first time, analyzed the presence of TXs and their metabolites in human urine. The findings revealed that 2-ITX (2-isopropylthioxanthone) and DETX (2,4-diethylthioxanthone) were more frequently detected than other TXs, displaying the detection frequencies of 82% and 79%, respectively, in human urine. Measured mean levels of 2-ITX and DETX were 0.66 ng/mL and 0.51 ng/mL, respectively, in human urine. Female participants (0.67 ± 0.24 ng/mL) demonstrated higher (p < 0.01) urinary concentrations of DETX than male participants (0.42 ± 0.19 ng/mL). Human urinary levels of 2-isopropy1-10-oxothioxanthen-9-one (p = 0.011), 2-diisopropy1-10,10-dioxothioxanthen-9-one (p < 0.01), and DETX (p = 0.011) were negatively correlated with the age of individual participants. The calculated mean daily exposure value of 2-ITX (240 ng/kg bw/day) was much (p < 0.01) higher than that of DETX (151 ng/kg bw/day) for the participants. This study offers foundational information on human exposure to TXs, contributing to future environmental health research and the development of human exposure management strategies.